Development of Basic Infrastructure: An Analysis of South 24 Parganas District in West Bengal, India - Bagchiz, Emon (Bulletin of Geography. Socio-economic Series, 2017)
Infrastructure provides the fundamental basis for socio-economic development of any country. It acts as the backbone of an economy. Regional disparities in infrastructural development naturally result in uneven development. Infrastructural development has greater significance in less developed areas due to their various inherent deficiencies and imbalances. With regard to this, status of the basic sectors of the infrastructure of South 24 Parganas district of West Bengal, India has been discussed in this article. This is a less developed area. Comparative analysis on infrastructural achievements at sub-district level has also been made. The study not only points towards the lack of uniform infrastructural development over the entire region, but also towards a tendency for concentration of such growth process in those areas of the district which lie in close proximity to the metropolis of Kolkata .